Electronic and optical properties of (Al xGa 1-x) 1-yMn yAs single crystal: A new candidate for integrated optical isolators and spintronics - Merabet, Boualem; Yarub, Al-Douri, Prof. Dr.; Abid, Hamza; Ali Hussain, Reshak, Prof. Dr. (Springer Science+Business Media, LLC, 2013)
Link to publisher's homepage at http://link.springer.com/